Electric field response of molecular reactivity descriptors: a case study - Kar, Rahul; Pal, Sourav (Theoretical Chemistry Accounts, 2008)
In the present article, we study the influence of external electric field on the density-based global and local reactivity descriptors using examples of some planar nonlinear polyatomic molecules with C-2V point group symmetry. The study mainly involves the application of weak electric field in a direction along the principal axis and along its perpendicular direction. We also discuss the strength of the electric field studied in this work in terms of the strength of the molecular interaction. The work is expected to throw light on the effect of interactions within the above range on reactivity descriptors. Results are presented for a few prototype molecules.
Keywords: electric field; molecular interaction; planar nonlinear polyatomic molecules; Reactivity descriptors

Molecular elucidation of pancreatic elastase inhibition by baicalein - Ghosh, Debajeet; Bansode, Sneha; Joshi, Rakesh; Kolte, Baban; Gacche, Rajesh (Journal of Biomolecular Structure & Dynamics, 2022)
The serine protease, elastase exists in various forms and plays diverse roles in the human body. Pharmacological inhibition of elastase has been investigated for its therapeutic role in managing conditions such as diabetes, pneumonia and arthritis. Sivelestat, a synthetic molecule, is the only elastase inhibitor to have been approved by any major drug regulatory authority (PMDA, in this case) - but still has failed to attain widespread clinical usage owing to its high price, cumbersome administration and obscure long-term safety profile. In order to find a relatively better-suited alternative, screening was conducted using plant flavonoids, which yielded baicalein, a molecule that showed robust inhibition against Pancreatic Elastase inhibition (IC50: 3.53 mu M). Other than having a considerably lower IC(50)than sivelestat, baicalein is also cheaper, safer and easier to administer. While MicroScale Thermophoresis validated baicalein-elastase interaction, enzyme-kinetic studies, molecular docking and molecular dynamic simulation revealed the mode of inhibition to be non-competitive. Baicalein exhibited binding to a distinct allosteric site on the enzyme. The current study demonstrates the elastase inhibition properties of baicalein in an in-vitro and in-silico environment.
Keywords: Baicalein; elastase; Enzyme inhibition; molecular interaction; sivelestat